Chronic wounds: Treatment consensus. Issue 2 (7th February 2022) - Eriksson, Elof; Liu, Paul Y.; Schultz, Gregory S.; Martins‐Green, Manuela M.; Tanaka, Rica; Weir, Dot; Gould, Lisa J.; Armstrong, David G.; Gibbons, Gary W.; Wolcott, Randy; Olutoye, Oluyinka O.; Kirsner, Robert S.; et al.
Abstract: The Wound Healing Foundation (WHF) recognised a need for an unbiased consensus on the best treatment of chronic wounds. A panel of 13 experts were invited to a virtual meeting which took place on 27 March 2021. The proceedings were organised in the sub‐sections diagnosis, debridement, infection control, dressings, grafting, pain management, oxygen treatment, outcomes and future needs. Eighty percent or better concurrence among the panellists was considered a consensus. A large number of critical questions were discussed and agreed upon. Important takeaways included that wound care needs to be simplified to a point that it can be delivered by the patient or the patient's family. Another one was that telemonitoring, which has proved very useful during the COVID‐19 pandemic, can help reduce the frequency of interventions by a visiting nurse or a wound care center. Defining patient expectations is critical to designing a successful treatment. Patient outcomes might include wound specific outcomes such as time to heal, wound size reduction, as well as improvement in quality of life. For those patients with expectations of healing, an aggressive approach to achieve that goal is recommended. When healing is not an expectation, such as in patients receiving palliative wound care, outcomes might include pain reduction, exudate management, odour management and/or other quality of life benefits to wound care.